Kualitas Organoleptik dan Mikrobiologis Daging Domba Menggunakan Ekstrak Pangium Edule Terhadap Masa Simpan - Peni Patriani; Harapin Hafid; Tri Hesti Wahyuni; Edhy Mirwandhono (JURNAL GALUNG TROPIKA, 2020)
Pangium edule or keluwak is a local spice that can extend the shelf life of livestock products because it contains antimicrobial compounds. This study aimed to determine the effect of marination using Pangium edule on the microbiological and organoleptic quality of lamb. This study used a factorial completely randomized design to treat Pangium edule concentration and shelf life of 3 replications each. Lamb meat was marinated using Pangium edule extract 0%, 3%, 6%, and 9%, then stored at 12 hours, 24 hours, and 36 hours at room temperature. The results showed that the longer the meat's shelf life, the microbial growth also increased, but marination using Pangium edule resulted in lower microbial growth than without treatment. The treatment of lamb marination with 3% and 6% Pangium edule extract showed the lowest microbes and was very significantly different from lamb without treatment for 36 hours. Its means that the antibacterial compound in Pangium edule can inhibit microbial growth and is still by the standards set by SNI compared to the control. Marination using Pangium edule extract during the shelf life also significantly affected the panelists' acceptance level, namely aroma, taste, tenderness, and color. Organoleptic scores, namely smell, taste, tenderness, and color at 6% to 9% with a shelf life of 36 hours, are still in a fairly good range. Marination using Pangium edule 6% can maintain the microbiological and organoleptic lamb quality for 36 hours.